Partisan nation the dangerous new logic of American politics in a nationalized era - Pierson, Paul 1959-; Schickler, Eric 1969- (The University of Chicago Press, 2024)
"American democracy is in trouble. At the heart of the contemporary crisis is a mismatch between America's Constitution and today's nationalized, partisan politics. Although American political institutions remain federated and fragmented, the ground beneath them has moved, with the national subsuming and transforming the local. In this brilliant, paradigm-shifting book, political scientists Paul Pierson and Eric Schickler bring today's challenges into new perspective. Attentive to the different coalitions, interests, and incentives that define the Democratic and Republican parties, they show how contemporary polarization emerged in a rapidly nationalizing country and how it differs from polarization in past eras. In earlier periods, three key features of the political landscape-state parties, interest groups, and media-varied locally and reinforced the nation's stark regional diversity. They created openings for new policy demands and factional divisions that disrupted party lines."